Tunable notch response for ultra wide-band bandpass filter - Jiim, Anthony Bruster; Zakaria, Zahriladha; Mutalib, Mohamad Ariffin; Saifullah, Nasrullah; Hashim, Norlezah; Ruslan, Eliyana (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
A design of ultra wide-band microstrip bandpass filter with tunable notch response of wireless communication system is presented in this paper. The five order bandpass filter is designed using optimum distributed highpass integrated with Defected Microstrip Structure (DMS). The bandpass filter was designed at wideband frequency from 3.1GHz to 10.6GHz. The insertion loss and return loss of this project is set to better than 0.5dB and 20dB respectively. The DMS is implemented in this design in order to remove undesired frequency in wireless communication system. The pin diode is added to act as a switch to tuning the notch response. When the pin diode off, the notch response produce a sharp response at 5.906GHz (WLAN). When the pin diode on, the notch response is removed from the passband and provide full UWB passband. This design is simulated by ADS software and using Roger Duroid 4350B with a dielectric constant of 3.48, substrate thickness 0.508mm and loss tangent 0.0019.